Study on the use of intravascular ultrasound-guided coronary intravascular lithotripsy compared with rotational atherectomy: a single-center, retrospective study - Ben Li; Jiaxing Li; Guangxin Hu; Shichang Zhang; Yongkang Ren; Mingyang Li; Yinping Li; Shaobin Jia (Journal of International Medical Research)
Objective This study aimed to compare the efficacy and safety of intravascular ultrasound (IVUS)-guided coronary intravascular lithotripsy and rotational atherectomy in treating severe coronary artery calcification. Methods A retrospective analysis of 60 patients who underwent percutaneous coronary intervention at the General Hospital of Ningxia Medical University from October 2022 to August 2023 was conducted. The patients were divided into two groups: 30 received IVUS-guided coronary intravascular lithotripsy and 30 underwent IVUS-guided rotational atherectomy. The primary endpoints comprised angiographic thrombolysis in myocardial infarction III flow and <30% stenosis post-percutaneous coronary intervention, and IVUS metrics, such as >80% stent expansion, avoiding high plaque burden or lipid-rich plaques, minimizing malapposition <0.4 mm/1 mm, and preventing tissue prolapse and dissection. Safety was assessed by complications and 1- and 6-month postoperative major adverse cardiovascular event rates. Results The primary endpoint was achieved in both groups. The treatment efficacy was 100% in all cases. At 1 and 6 months post-procedure, there was no significant difference in major adverse cardiovascular events, acute myocardial infarction, or stent thrombosis between the two groups. Conclusion IVUS-guided coronary intravascular lithotripsy is a safe and effective alternative to rotational atherectomy, potentially reducing certain complications.